The Dialectic of Aisha Abdurrahman’s Literary Tafsir and Nasr Hamid Abu Zayd’s Hermeneutics in Constructing the Integrity of Contemporary Islamic Scholarship - Muhammad Aminullah (Universitas Islam Cordoba Banyuwangi, 2025)
This study explores the epistemological dialectic between Aisyah Abdurrahman’s literary exegesis and Nasr Hamid Abu Zayd’s hermeneutics as two modern intellectual projects in understanding the Qur’an. The research aims to identify how both methods contribute to the reconstruction of Qur’anic interpretation in the contemporary era and their implications for Islamic intellectual civilization. Using a qualitative library research method, the study analyzes primary tsexts al-Tafsīr al-Bayānī li al-Qur’ān al-Karīm and Mafhūm al-Naṣṣ through a comparative-descriptive approach. The findings reveal that Aisyah Abdurrahman emphasizes the linguistic purity of revelation as a form of harmony between language, faith, and reason, while Abu Zayd situates the Qur’an within a historical and cultural framework that highlights its humanistic dimensions. The dialectic between both reflects a dynamic interaction between revelation and reason, preserving the balance between transcendence and contextual interpretation. This study concludes that Qur’anic interpretation should integrate textual sanctity, rational analysis, and cultural to sustain the continuity of Islamic knowledge and civilization.